Implementasi Outcome-Based Education (OBE) dan Benchmarking Internasional dalam Pengabdian Mahasiswa melalui Pengelolaan Stok Opname di RIC : Penerapan Outcome Based Education dalam Manajemen Stok Opname di Learning Factory - Fitra Putri Oganda; Syifa Wulandari; Vivi Meilinda; Alessandro Rossi; Miftakhul Khasanah (ADI Publisher, 2025)
In the era of globalization and digital transformation, efficient stock opname management is crucial for business sustainability. Higher education institutions play a key role in preparing students with practical competencies relevant to industry needs. This community service focuses on stock opname management at Learning Factory Raharja iCafe (RIC), applying Outcome-Based Education (OBE) to provide students with practical experience in more efficient inventory management. The method used is SWOT (Strengths, Weaknesses, Opportunities, and Threats), identifying strengths, weaknesses, opportunities, and threats in stock opname management at RIC. Data was collected through interviews with academic leaders and RIC staff to analyze the impact of OBE on stock management. The results indicate that the application of OBE significantly contributes to improving stock opname efficiency, including reducing waste and improving inventory data accuracy. This community service project successfully made a positive impact on stock management quality and student competency development, while supporting the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 12 (Responsible Consumption and Production).